A false positive result in prenatal trisomy screening and its association with maternal psychological distress - Määttänen, Sini (My University, 2022)
Prenatal screening for fetal trisomy 21 (Down syndrome) is offered to all pregnant women in Finland. In case of a positive screening test result, an invasive diagnostic test can be made to assess the fetal karyotype. Most of the positive screening results are false positives. The aim of this study was to find out if mothers receiving a false positive screening result are more distressed in pregnancy than controls, and how a normal result in fetal karyotyping affects maternal psychological distress. The study population was drawn from the FinnBrain Cohort Study. As cases we included subjects with an increased risk for fetal abnormality based on first-trimester trisomy screening or ultrasound screening, following a normal result in invasive testing (n=53). The rest of the cohort (n=2286) served as controls. Maternal depressive and anxiety symptoms were measured with the Edinburgh Postnatal Depression Scale (EPDS) and Symptom Checklist 90 (SCL-90) at 14, 24 and 34 gwks. The questionnaire scores of the cases were compared to those of the controls. No significant differences in EPDS or SCL scores were observed between the groups at any of the timepoints assessed. However, EPDS scores decreased significantly from 14 to 24 gwks among the cases, whereas among the controls there was no difference (median -1,0 for cases and 0,0 for controls, P=0.003). Our results suggest that a false positive screening result in chromosomal abnormality screening is not associated with prolonged psychological distress. On the other hand, a normal result in fetal karyotyping seemed to alleviate depressive symptoms.